A novel concept of passive loop-forming wire-guided biliary cannulation using an ultra-deep angled tip guidewire (with video) - Ban, Tesshin; Kubota, Yoshimasa; Takahama, Takuya; Sasoh, Shun; Tanida, Satoshi; Ando, Tomoaki; Nakamura, Makoto; Joh, Takashi (Endoscopy International Open, 2023)
Background and study aims Wire-guided biliary cannulation (WGBC) is a standard technique during endoscopic retrograde cholangiopancreatography-related interventions. However, no dedicated guidewire is available. We investigated a novel “passive loop-forming WGBC” concept using a 0.035-inch ultra-deep angled tip guidewire.Patients and methods This single-arm, single-center, retrospective study included consecutive 111 patients who underwent passive loop-forming WGBC as the first biliary intervention between October 2021 and December 2022.Results WGBCs were completed within 5 minutes and overall were performed at a median papillary negotiation time of 81 seconds (interquartile range [IQR], 39–170) and 114 seconds (IQR, 49–303) in 83 (74.8%) and 106 (95.5%) cases, respectively. Logistic regression analysis identified age ≥ 80 years (odds ratio [OR]: 3.56, 95% confidence interval [CI]: 1.12–11.31) and unintentional pancreatic guidewire insertion (OR: 17.67, 95% CI: 5.75–54.31) as significant risk factors for failed WGBC within 5 minutes. Among the 106 obtained cannulations, the guidewire leading part formed a small-looped tip and wide-looped body in 83 (78.3%) and 23 (21.7%) cases, respectively. Adverse events included post-procedure pancreatitis (2/111 [1.8%]) and guidewire penetration (3/111 [2.7%]).Conclusions Passive loop-forming WGBC using an ultra-deep angled tip guidewire is a feasible procedure.
Keywords: Pancreatobiliary (ERCP/PTCD); ERC topics; Quality and logistical aspects; Performance and complications